Características hidrológicas da bacia hidrográfica do rio Xingu e modelo de previsão fluviométrica para Altamira-PA - SANTOS, Cleber Assis dos (2019)
The necessity of understanding the variability of the spatial distribution of rainfall is extremely important for the development and planning of the water resources management. The characterization has wide application as an indicator to predict the degree of vulnerability of the basin phenomena like floods, inundations and others. In the Xingu River Basin, it stands out the municipality of Altamira - PA, the largest municipality in the world. The head municipality is located alongside the Xingu River and historically suffers extreme events of floods that cause inundations, causing great damage to the population that lives surrounding the Xingu River, displacing families and causing social vulnerability. The objective of this work is developing a Fluviometric Forecasting Model (quota-flow) for the city of Altamira - PA, due to the seasonality of the hydrological characteristics of the Xingu River Basin. For the statistical analysis of rainfall and fluviometric data, the procedure was: verification of the independence of the time series by serial autocorrelation and application of the trend test (Mann-Kendall) to test the performance of the proposed model, in relation to data about the measured and estimated quota, they were used the Nash-Sutcliffe coefficient and the coefficient of determination, through the softwares Microsoft Excel 2013 and Statistica 10.0. The proposed model proposed in this work, Hydrologic Forecasting Model Xingu Altamira – MOPHIXA, makes the prediction before two months of the occurrence of the monthly average of fluviometric quota of the Xingu River at Altamira - PA, through the cumulative monthly average of rainfall in the Xingu River Basin. In addition, using the rating curve it is possible to find the Xingu River flow in Altamira - PA based on fluviometric quota predicted by the model. According to the historical serie data (1985 to 2013), it was noticed that the annual average rainfall is 1963.5 mm for the Xingu River Basin. The lower course (Altamira Station) registered flow values exceeding 17000 m³/s, which concentrate the maximum of rainfall, exceeding 2200 mm, characterizing the largest hydropower potential in this region. The performance measures considered in the validation of this forecasting model showed good results, with the Nash-Sutcliffe coefficient is equal to NS = 0.83 and the determination coefficient is equal to R² =0.86. These models are very important to understand the seasonality of events like floods and drought in the Xingu River, being fundamental to be able to provide informations to the decision-making process in the city of Altamira - PA.